AB0591 Acute Respiratory Failure – the Reason for Urgent Rheumatologic Examination?. (10th June 2014) - Bradna, P.; Manak, J.; Koblizek, V.; Soukup, T.; Toms, J.; Tosovsky, M.; Kodeda, M.; Nikolov, D.H.
Abstract : Background: Acute respiratory failure is a reason for urgent admission to ICU. Statistical data show, that about 10 percent of deaths of respiratory failure patients on ICU is caused by diffuse alveolar hemorrhage syndrome (DAH). Barring infection, coagulation defects or oncological therapy complications, systemic connective tissue diseases must be considered as a reason. Less frequently there are patients with known systemic disease, more frequently DAH is the first manifestation of connective tissue disease, especially systemic vasculitis or SLE. Methods: During 8 years 24 cases of diffuse alveolar hemorrhage in rheumatologic diseases were treated, 22 on ICU. 21 of them needed artificial ventilation. We observed the symptoms of preceded systemic disease, autoantibodies in time of DAH, hospital mortality and follow up of patients. Results: 13 women and 11 men were affected, average age was 52, 6 (21-74) years. Only in 32% of them had known diagnosis of systemic connective tissue disease before episode of alveolar hemorrhage. Diagnose of DAH was assessed by bronchoscopy with examination of bronchoalveolar lavage fluid and X-ray or CT results. 21 patients needed artificial ventilation.Most frequent immunological feature was ANCA antibody in 75% of our group. Proteinase -3 specificity was present in 58%, myeloperoxidase in 16% of our patients. ANA antibodies were founded in 21% of our patients, in one patient there was atypical anti GBM antibodies.Antiphospholipid antibodies were not present. Negative results had 20, 8% of our group. Patients were treated by pulse methylprednisolone therapy, plasmapheresis, and i.v. Cyclophosphamide or i.v. immunoglobulins in cases where immunosuppressive therapy was contraindicated. Hospital mortality was 42 percent (10 patients). 14 patients are followed on outpatient base, in 3 of them chronic hemodialysis for irreversible renal failure is necessary, Early diagnosis and start of intensive immunomodulating therapy were one of crucial factors for survival of this life-threatening complication, however intensive immunosuppression is high-risky in patients with artificial ventilation support. Conclusions: Diffuse alveolar hemorrhage is one of the important reasons of acute respiratory failure. In significant part of such patients the systemic connective tissue disease, mostly systemic vasculitis, is the cause of complication. Serious episode of DAH may be the first manifestation of rheumatologic disease. Bronchoscopic examination for DAH may be performed as early as possible, therefore early start of immunosuppressive therapy is crucial for survival of such patients. Outside of bronchoscopy instant assessment of ANCA antibodies is helpful. References: West S, Arulkumaran N, Ind PW, Pusey CD Diffuse alveolar haemorrhage in ANCA-associated vasculitis. Intern Med. 2013;52(1):5-13. Acknowledgements: Supported by MH CZ - DRO (UHHK, 00179906) Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4884